Working Capital and Investment Financing in the MSME Sector: Impact on the Profitability of Islamic Commercial Banks in Indonesia - Yaman, Afdhal; Hamizar, Arizal (JURNAL EKONOMI SYARIAH, 2023)
Introduction to The Problem: MSMEs face several conservative challenges, such as financing constraints. This opportunity can be the primary concern of how working capital financing and investment financing in the MSME sector benefit Islamic Commercial Banks.Purpose/Objective Study: This study examines the impact of working capital and investment financing in the MSME sector on Islamic Commercial Banks' profitability in Indonesia.Design/Methodology/Approach: The quantitative research method uses the EViews 10 application. The data used in this study is data on Islamic Commercial Banks in Indonesia from June 2014 - February 2023. Observations were made on 105 time series data observations.Findings: Working capital financing in the MSME sector does not significantly impact the profitability of Islamic Commercial Banks in Indonesia. However, investment financing for the MSME sector has a positive and significant impact on the profitability of Islamic Commercial Banks in Indonesia at a significance level of 1%. Thus, the more investment financing provided to the MSME sector, the higher the profitability level of Islamic Commercial Banks. Therefore, Islamic Commercial Banks in Indonesia should be more focused on providing investment financing to the MSME sector to increase the profitability and growth of Islamic Commercial Banks in Indonesia.Paper Type: Research Article